Combined effect of cabozantinib and gefitinib in crizotinib‐resistant lung tumors harboring ROS1 fusions. Issue 10 (11th September 2018) - Kato, Yuka; Ninomiya, Kiichiro; Ohashi, Kadoaki; Tomida, Shuta; Makimoto, Go; Watanabe, Hiromi; Kudo, Kenichiro; Matsumoto, Shingo; Umemura, Shigeki; Goto, Koichi; Ichihara, Eiki; Ninomiya, Takashi; et al.
Abstract : The ROS1 tyrosine kinase inhibitor (TKI) crizotinib has shown dramatic effects in patients with non‐small cell lung cancer (NSCLC) harboring ROS1 fusion genes. However, patients inevitably develop resistance to this agent. Therefore, a new treatment strategy is required for lung tumors with ROS1 fusion genes. In the present study, lung cancer cell lines, HCC78 harboring SLC34A2‐ROS1 and ABC‐20 harboring CD74‐ROS1, were used as cell line‐based resistance models. Crizotinib‐resistant HCC78R cells were established from HCC78. We comprehensively screened the resistant cells using a phosphor‐receptor tyrosine kinase array and RNA sequence analysis by next‐generation sequencing. HCC78R cells showed upregulation of HB‐EGF and activation of epidermal growth factor receptor (EGFR) phosphorylation and the EGFR signaling pathway. Recombinant HB‐EGF or EGF rendered HCC78 cells or ABC‐20 cells resistant to crizotinib. RNA sequence analysis by next‐generation sequencing revealed the upregulation of AXL in HCC78R cells. HCC78R cells showed marked sensitivity to EGFR‐TKI or anti‐EGFR antibody treatment in vitro. Combinations of an AXL inhibitor, cabozantinib or gilteritinib, and an EGFR‐TKI were more effective against HCC78R cells than monotherapy with an EGFR‐TKI or AXL inhibitor. The combination of cabozantinib and gefitinib effectively inhibited the growth of HCC78R tumors in an in vivo xenograft model of NOG mice. The results of this study indicated that HB‐EGF/EGFR and AXL play roles in crizotinib resistance in lung cancers harboring ROS1 fusions. The combination of cabozantinib and EGFR‐TKI may represent a useful alternative treatment strategy for patients with advanced NSCLC harboring ROS1 fusion genes. Abstract : Comprehensive gene profiling revealed that HB‐EGF and AXL were overexpressed in crizotinib‐resistant lung cancer cells. Activation of EGFR induced by HB‐EGF rendered lung cancer cells harboring ROS1 fusion genes resistant to crizotinib. Combination of ROS1/AXL inhibitor, cabozantinib and EGFR‐TKI (gefitinib) showed an excellent inhibitory effect in the crizotinib‐resistant cells in vitro and in vivo.